Emergency psychiatric nursing: A concept analysis - Pragholapati, Andria; Ismail, Suhartini (Majalah Kesehatan Indonesia, 2024)
Background: Individuals with Mental Disorders (ODGJ) are at risk of relapse, leading to emergencies. Untreated psychiatric emergencies can result in disability or even death. Emergency psychiatric care, if not promptly addressed, poses a crucial and complex topic. The aim of this research is to define and clarify these essential concepts, integrating them into mental health nursing care. Methods: Literature search employed keywords such as "emergency" AND "psychiatric" AND "nursing" in English databases (including PubMed, ScienceDirect, and CINAHL) without time restrictions. After extracting concept definitions and identifying characteristic features, psychiatric emergency nursing care was defined. Subsequently, case samples, antecedents, consequences, and empirical concept references were determined. Results: After reviewing four articles, psychiatric emergency nursing care was defined with the following attributes: "adequate response to psychiatric patients," "prompt care for patients with mental health issues should be simple and fast," and "stigma associated with those facing mental health problems." Conclusion: Mental health nursing care can utilize these findings for interventions, evaluating psychiatric emergency nursing care, and training high-quality nurses.